2015
DOI: 10.1016/j.antiviral.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Targeting host lipid synthesis and metabolism to inhibit dengue and hepatitis C viruses

Abstract: Lipids are necessary for every step in the replication cycle of hepatitis C virus (HCV) and dengue virus (DENV), members of the family Flaviviridae. Recent studies have demonstrated that discrete steps in the replication cycles of these viruses can be inhibited by pharmacological agents that target host factors mediating lipid synthesis, metabolism, trafficking, and signal transduction. Despite this, targeting host lipid metabolism and trafficking as an antiviral strategy by blockade of entire pathways may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 98 publications
0
64
0
Order By: Relevance
“…It has been suggested that DENV modulates the cellular lipid metabolism in order to boost de novo synthesis of membranous systems (replicative complexes) for viral replication [22,30,49,50]. The antiviral properties of drugs that disrupt fatty acid and cholesterol biosynthesis pathways against DENV suggest a pivotal role for lipidic content during the infection process [2628].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that DENV modulates the cellular lipid metabolism in order to boost de novo synthesis of membranous systems (replicative complexes) for viral replication [22,30,49,50]. The antiviral properties of drugs that disrupt fatty acid and cholesterol biosynthesis pathways against DENV suggest a pivotal role for lipidic content during the infection process [2628].…”
Section: Discussionmentioning
confidence: 99%
“…For example, RNA viruses such as hepatitis C and dengue virus promote efficient replication by altering host lipid metabolism [19]. Adenovirus can perturb the function of the transcription factor MYC to promote glucose and glutamine metabolism [20], and Kaposi’s Sarcoma-associated Herpesvirus (KSHV) has also been shown to induce MYC expression leading to increased glutaminolysis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, pharmacological manipulation of cellular lipid metabolism is rising as an alternative potential strategy to combat these pathogens (7,8). Along these lines, we have shown that the hypolipidemic compound NDGA and its synthetic derivative M 4 N exhibit potent antiviral activity against WNV and ZIKV.…”
Section: Discussionmentioning
confidence: 97%
“…Considering this dependence on lipid metabolism during flavivirus infection, pharmacological modification of the lipid metabolic pathways appears to be a proper strategy to impair flaviviral replication (7,8). Along these lines, the hypolipidemic drug nordihydroguaiaretic acid (NDGA) has been reported to inhibit replication of the flavivirus DENV (9).…”
mentioning
confidence: 99%